(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
With this paper I would like to show several unpublished materials, with a possible paleohispanical caracter, documented by Juan Cabré in the Catalogos Monumentales of the provinces of Soria and Teruel. These pieces are two possible tesserae hospitalitatis, one with dolphin-shape, and the other with human-headed shape; two groups of rock-carved inscriptions from Torrevicente and from Concud; and a celtiberian rock-engraved that represent a singular fighting.